Reconstructions for Analytic Signals Based on Greedy Algorithm - Shuang, Li (Journal of physics. Conference series, 2021)
In this paper, we utilize greedy algorithm to approximate analytic signals and transfer functions sparsely. Based on reproducing kernels of Hardy space, a redundant dictionary is constructed. The approximating strategy relies on matching pursuit which is an implementation of greedy algorithm. A numerical example and Python codes are provided to illustrate the idea.